A comparison of the mechanical effect of arm swing and countermovement on the lower extremities in vertical jumping - Hara, M.; Shibayama, A.; Takeshita, D.; Hay, D. C.; Fukashiro, S. (Human Movement Science, 2008)
The purposes of this study were to quantify and compare how arm swing and countermovement affect lower extremity torque and work during vertical jumping and to gain insight into the mechanisms that enable the arm swing and countermovement to increase jump height. Five participants maximally performed two types of vertical squat jumps with (SJA) and without (SJ) an arm swing and two types of countermovement vertical jumps with (CJA) and without (CJ) an arm swing. The participants jumped from a force platform and all performances were videotaped with a high-speed video camera (200 Hz). Jump heights, joint torques and work were calculated by combining kinematic and kinetic data. It was found that of the four jumping conditions, the participants jumped highest when they used an arm swing with countermovement (i.e., CJA). The increase of the countermovement jump height with an arm swing is the result of the increase of the lower extremity work. In the hip joint, the increase in torque caused by the countermovement predominantly occurred at the beginning of the propulsion phase, while the increase in torque caused by the arm swing occurred in the rest of the propulsion phase. A key finding of our study is that arm swing and countermovement have independent effects on lower extremity work, and their effects are additive in CJA to produce greater jump height.